Probiotic Weizmannia coagulans MTCC 5856 as adjunct therapy in children's acute diarrhea—a randomized, double-blind, placebo-controlled study - Majeed, Muhammed; Nagabhushanam, Kalyanam; Arumugam, Sivakumar; Chadalavada, Nagarjuna; Seepana, Jyotsna; Annamalai, Thumjaa; Murali, Avinash; Prakasan, Priji; Mundkur, Lakshmi (Frontiers in Pediatrics, 2024)
Objectives Acute diarrhea in children is generally managed by replacing the lost fluid with oral rehydration solution (ORS). Probiotic supplementation has been reported to reduce the severity of diarrhea. In the present study, we investigated the effect of Weizmannia coagulans (Bacillus coagulans) MTCC 5856, along with ORS on acute diarrhea of all causes in non-hospitalized children. Methods A total of 110 children of ages between 1 and 10 were enrolled in a double-blind placebo-controlled study and were randomly allocated to receive W. coagulans MTCC 5856 (4 × 108 spores, N = 54) + ORS and zinc (Zn) or a placebo (N = 56) + ORS and (Zn) for 5 days. The consistency of the stool, mean duration of diarrhea in hours, mean diarrhea frequency per day, and the dehydration status were collected as efficacy endpoints. Safety was evaluated by the occurrence of adverse events. Results The mean age of the children was 5.55 ± 2.57 years (61 boys and 49 girls). The mean duration of diarrhea was 51.31 ± 20.99 h in the W. coagulans MTCC 5856 group and 62.74 ± 24.51 h in the placebo (p = 0.011) group. The frequency of diarrhea was lower in children supplemented with the probiotic, but the difference was not statistically significant. The perceived efficacy score and dehydration status improved significantly in the W. coagulans MTCC 5856 group compared with the placebo group. No adverse events were recorded. Conclusion The results of the study suggest that W. coagulans MTCC 5856 could be supplemented along with ORS and zinc to reduce the duration of diarrhea in non-hospitalized children. Clinical Trial Registration ClinicalTrials.gov, identifier CTRI/2022/06/043239.